CLASSROOM MANAGEMENT PRACTICES ADOPTED BY TEACHERS FOR PROMOTING ACADEMIC ENGAGEMENT IN PUBLIC SECONDARY SCHOOLS IN ANAMBRA STATE (UNIZIK Journal of Educational Management and Policy, 2026)
The study examined teacher’s use of appropriate teaching methods and effective communicationskills as classroom management practices for promoting student’s academic engagement inAnambra State. Two research questions guided the study while two hypotheses were tested at0.05 alpha level. A descriptive survey research design was adopted for the study. The populationof the study comprised of 1072 male and 6176 female teachers making 7,248 in the 267 schoolsin the six education zones of Anambra State. A sample size of 487 made up of 64 male and 423female teachers in government owned secondary schools in the selected Education Zones wasdrawn using multistage sampling procedure. A researcher-developed questionnaire title Teachers’Classroom Management Practices for Promoting Students’ Academic Engagement in SecondarySchool (TCMPPSAESS) was used for data collection. The instrument was validated by threeexperts. The reliability of the instruments was established using Cronbach alpha method. Thereliability of instrument coefficients obtained was an overall index of 0.986. In answering theresearch questions and testing the hypotheses, descriptive (mean and standard deviation) andinferential (t-test) statistics were used. The findings revealed among others that teachers' use ofappropriate teaching methods, and effective use of communication skills promote students’academic engagement. The study concluded that both female and male teachers' use ofappropriate teaching methods, and effective use of communication skills as classroommanagement practices promote students' academic engagement in Anambra State and thusrecommended among others that curriculum planners should propose more effective strategiesthat would continue to enhance teachers’ classroom management practices for better engagementof students academically in Anambra State.
Keywords: Teacher, Classroom Management Practices, Academic Engagement